Elevating property management in public housing: A systematic literature review - Teo, Jes She; Mohd Aini, Ainoriza; Zyed, Zafirah Al Sadat (International Journal of Strategic Property Management, 2024)
Public housing (PH) focuses on assisting low-income households with housing stability. However, the inefficiency of property management in PH gives rise to a range of challenges in both physical and internal operational management, leading to negative stigmatisation towards tenants living in PH. Various initiatives have been launched to address the inefficiencies of property management. This study categorised and elaborated these initiatives under three main categories: reconceptualisation, externalisation, and managerialisation. There is currently no systematic literature review that provides a comprehensive overview of the initiatives aimed at enhancing property management in PH on a global scale, despite the fact that an overwhelming number of initiatives have been proposed in various studies. Therefore, the present systematic literature review was conducted to provide a comprehensive understanding of the existing research and initiatives pertinent to PH property management. This thorough examination will not only inform the current state of property management practices but also provide valuable insights to guide future research endeavours and decision-making processes in this domain. The outcome of this study revealed the positive impact of managerialisation, showcasing its pivotal role in problem identification and as a strategic indicator for proposing solutions aimed at continuous improvement.